Men and obesity: what are the issues?. Issue 1 (January 2017) - Haslam, David
Abstract : Obesity is a major and growing problem for men in the UK. In this article Professor Haslam describes the damaging health consequences of obesity, the obesity paradox, and traces the journey that now puts carbohydrate in the frame in place of fat.